An Analysis of Teacher Beliefs and Practices in Grammar Teaching: A Case Study of EFL High School Teachers - Sabita, Mutyara; Pujiawati, Nia; Fauzi Miftakh, Fauzi Miftakh (FKIP-Universitas Riau, 2024)
This study aimed to explore teachers' beliefs about grammar teaching. Using a qualitative case study design, the researcher conducted interviews and observations to collect data. The data analysis method was adopted from Miles and Huberman (1994). The findings revealed a strong alignment between teachers' stated beliefs about grammar and their actual teaching practices. This consistency suggests that teachers effectively translated their beliefs into actions during lessons. Such alignment is expected to contribute positively to the overall teaching and learning process, as it ensures that the instructional methods are in harmony with the teachers' perspectives on grammar. The study highlights the importance of understanding teachers' beliefs as a key factor in improving grammar instruction.